# Solve for x and y:2x + 3y + 1 = 0,

After rearrangement, we have

2x + 3y = - 1 …eq.1

…eq.2

Let us first simplify eq.2 by taking LCM of denominator,

Eq.1

7 – 4x = 3y

4x + 3y = 7 …eq.3

To solve these equations, we need to make one of the variables (in both the equations) have same coefficient.

And it is so that the equations 1 & 3 have variable y having same coefficient already, so we need not multiply or divide it with any number.

Recalling equations 1 & 3,

2x + 3y = - 1

4x + 3y = 7

On solving these two equations we get,

x = 4

Substitute x = 4 in eq.1/eq.3, as per convenience of solving.

Thus, substituting in eq.3, we get

4(4) + 3y = 7

16 + 3y = 7

3y = 7 – 16

3y = - 9

y = - 3

Hence, we have x = 4 and y = - 3

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Dealing With the Real Life Problems53 mins
Quiz | Solution of Linear Equations53 mins
Champ Quiz | Consistency and Inconsistency of Solutions36 mins
Pair of Linear Equations in Two Variables46 mins
Quiz | Real Life Problems Through Linear Equations56 mins
Dealing with the Real Life Problems54 mins
Smart Revision | Important Word Problems37 mins
Elimination (quicker than quickest)44 mins
Bonus on Applications of Linear Equations in Two Variables43 mins
HOT Topics of Applications of Linear Equations in Two Variables52 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses